PENDIDIKAN KARAKTER ISLAMI BAGI REMAJA DALAM KELUARGA DI KAMPUNG PADAS DESA SIDOMULYO KOTA BATU (STUDI KASUS PADA MASA PANDEMI COVID-19) - Vira Indrasanti; M. Ilyas Thohari; Fita Mustafida Mustafida (VICRATINA, 2022)
Character education must be instilled as early as possible when the child has begun to imitate the actions of the child's parents, starting to be directed to positive things that can be useful for him in society. A muslim is obliged to have the character of Islam as an identity to signify that he's a muslim. material character education in Islamic teaching by the family in Kampung Padas covers, religious character, the character of the moral, the character of the Al-Qur’an, and the character of the history of Islam. The implementation of character education has been started since young children with the use of print media such as books and electronics such as mobile phones and television, the methods used, among others, habituation, advice, motivation and punishment, the evaluation is also given by the family in Kampung Padas. The success of character education family teach rated quite well evidenced by children who are already able to carry out the duties and responsibilities of their own. This study uses a qualitative method in which data collection using the method of observation, interview and documentation as well as supported by an opinion from the experts.